Use of the HEC RAS model for the analysis of exceptional floods in the Ouémé basin - Amoussou, Ernest; AMOUSSOU, Félix; BOSSA, YAOVIE EYMARD; KODJA, D. Japhet; TOTIN VODOUNON, Sourou Henri; HOUNDENOU, Constant; BOKO, MICHEL (My University, 2023)
The Ouémé River basin extends over almost half of Benin’s territory, entirely located in a humid tropical climate. This river system includes a deltaic zone (delta of the Ouémé) known for its high agricultural potential and thus subject to a socio-economic development agenda. The Ouémé delta is facing recurrent floods that maintain rural agricultural population into a retrograding crisis with significant damages such as losses of properties. The objective of this study is to improve decision-making in the Ouémé basin through the simulation of exceptional floods using the HEC-RAS model. The HEC RAS model is a conceptual model, which works through mathematical and physical formulas to implement environmental phenomena for forecasting, understanding and analysis purposes. The model inputs used are basin GIS data, hydro-meteorological data, characteristics of existing hydraulic structures, etc. The targeted outputs include 1D/2D/3D view plans with support of satellite images, tables, graphs and curves. It is worth mentioning that the model provides outputs compatible with other tools, such as civil engineering (Civil 3D, Revit, Infraworks, etc.) and GIS, that help to expand the valorization fields. The implementation of the model in the Ouémé basin has made it possible to note: (i) that the recurring effect of losses and damages is justified by the settlement of the population on the river banks; (ii) that there is an important agricultural production in areas of high flood risk; (iii) that depending on the occurrence of the phenomenon, the flooded extent and the height of submersion remains variable, and more important for extreme flooding; (iv) about 12.07% occurrence of river flood against 13.24% for flash flood at a return period of 30 years. Moreover, it is very relevant to note that most of flood waters converge to the western part of the basin (an area with a low risk of flooding, stretched over 63.68 km2) and to the eastern part around the Damè-Wogon depression (an area at high risk of flooding, stretched over 10.49 km2).
Keywords: flood risk; flood damage estimation; Ouémé River; Basin; HEC-RAS model; exceptional flood